Pleural Mesothelioma in the Era of Immunotherapy - Mathieu Chevallier; Floryane Kim; Alex Friedlaender; Alfredo Addeo (Clinical Medicine Insights: Oncology, 2023)
Over the course of the last decade, immunotherapy has revolutionised the management of a great number of cancer types. The treatment of pleural mesothelioma, a rare and highly aggressive cancer, is also being transformed by immunotherapy. The recent combination of ipilimumab and nivolumab improved overall survival compared with platinum-based chemotherapy, irrespective of the histology, establishing immunotherapy as a front-line standard of care in advanced pleural mesothelioma. Yet, most patients do not derive long-term benefit from any of the available therapies, and we note a significant lack of predictive and prognostic biomarkers. After progressing on first-line therapy, patients have limited therapeutic options, and data are scarce about optimal sequencing. In this perspective, we discuss the current management of pleural mesothelioma, defining what we consider to be the therapeutic sequence based on performance status and tumour histology. We also highlight promising ongoing trials that could further shape the management of this rare disease.